Academic reawakening: Situated experiences of undertaking a post graduate masters course in dementia. (January 2020) - Burrow, Simon; Mairs, Hilary; Bradshaw, Timothy; Pusey, Helen; Keady, John
Abstract: Master's level education can play important function in developing the knowledge and skills for nurses and allied professionals working in advanced roles in dementia care. However, little is known about the challenges experienced by professionals when making the transition to post-graduate study. This was a qualitative study comprising individual interviews with 15 graduates, nine of whom were nurses, who had experience of attending a part-time Master's in Dementia Care in the Northwest of England. Four sequential themes emerged from the data: 'Deciding what to do', 'Taking it on', 'Keeping going' and 'Endings and New beginnings'. Findings confirmed that Master's education for nurses and other professionals is significant in developing knowledge and instilling confidence in changing practice. Nevertheless, professionals experienced challenges in juggling the competing demands of education, family and work and were seen to navigate and negotiate their student journey by drawing on internal resources and external supports. The study adds to evidence that Master's level study is likely to benefit practice in dementia care; however, employers and Higher Education Institutions need to develop effective and flexible supports to enable nurses and allied professionals to engage effectively in part-time taught post graduate education. Highlights: Post graduate education is important in developing skills for dementia care leaders. Graduates feel more confident and able to challenge practices and lead change. The experience of post graduate education can however be challenging. Students have to balance competing needs and adjust to new educational challenges. Programme design should incorporate supports to meet student needs.